2010
DOI: 10.1002/app.31110
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of resin IV: Salicylic acid, diaminonaphthalein, and formaldehyde terpolymer and its ion exchange

Abstract: This article reports the synthesis, characterization, and ion exchange properties of a terpolymer. The terpolymer resin salicylic acid-diaminonaphthaleinformaldehyde (SDNF) was synthesized by the condensation of salicylic acid and diaminonaphthalein with formaldehyde in the presence of a hydrochloric acid catalyst. Terpolymer resin was characterized by elemental analysis, infrared (IR) spectroscopy, nuclear magnetic resonance spectroscopy, and UV-Visible spectral studies. The number average molecular weight of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…The electrical conductance of polymeric material depends upon incalculable parameters such as porosity, pressure, method of preparation and atmosphere. Generally polymers containing aromatic nuclei and conjugated unsaturation centres in the back bone exhibit lower activation energy than those with aliphatic system 21,26,27. The powdered sample of resin SAMF-I was palatalized by hydraulic press at pressure of 17lb inch -2 .…”
Section: Electrical Conductivity Of Samf-i Resinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrical conductance of polymeric material depends upon incalculable parameters such as porosity, pressure, method of preparation and atmosphere. Generally polymers containing aromatic nuclei and conjugated unsaturation centres in the back bone exhibit lower activation energy than those with aliphatic system 21,26,27. The powdered sample of resin SAMF-I was palatalized by hydraulic press at pressure of 17lb inch -2 .…”
Section: Electrical Conductivity Of Samf-i Resinsmentioning
confidence: 99%
“…Rahangdale et al 7 carried out the study of terpolymeric resin and found that the electrical conductivity of each of the copolymer resins increases with increase in temperature. Electrical conductivity study has been done of resin synthesized from salicylic acid, butylenediamine and formaldehyde 8 . Dharkar et al 9 studied the conductivities of melamine-aniline-formaldehyde terpolymer resins and its polychelates.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are different methods reported in the literature for evaluation and characterization of ion exchange resins [8][9][10][11], but the isotopic tracers technique as one of the non destructive radio analytical technique offer several advantages such as high detection sensitivity, capability of in-situ detection, limited memory effects and physico-chemical compatibility with the material under study [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of their advanced stage of development, various aspects of ion exchange technologies have been continuously studied to improve the efficiency and economy of their application in radioactive waste management. Efforts to develop new organic ion exchangers for specific applications are continuing [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore development of new organic ion exchange materials for specific industrial and technological applications is a biggest challenge to present day researchers. Development of ion exchange resins is usually followed by characterization to understand the performance of those resins in various technological applications [5][6][7][8][9][10][11]. Although number of techniques are available for the characterization of ion exchange resins [12][13][14], but the radiotracer technique offer several advantages such as high detection sensitivity, capability of in-situ detection, limited memory effects and physico-chemical compatibility with the material under study [15,16].…”
Section: Introductionmentioning
confidence: 99%